Avaliação dos sistemas purinérgico e colinérgico no processo inflamatório de pacientes com síndrome metabólica - Martins, Caroline Curry (2012)
Metabolic syndrome (MetS) is characterized by the presence of set cardiovascular risk factors such as hypertension, hyperglycemia, dyslipidemia and abdominal obesity. This pathology has been widely discussed due to the impact of cardiovascular disease (CVD), has been a concern for public health. In addition to the classic risk factors of this syndrome, has been indicated the presence of a low-grade chronic inflammation in their patients, which is considered a key point in the development of atherosclerosis and CVD. Some inflammatory markers has been used in order to diagnose cardiovascular asymptomatic patients at risk, as the levels of C-reactive protein (CRP) and uric acid and the activity of myeloperoxidase enzyme (MPO). In addition, studies have shown close relation of the purinergic and cholinergic systems in control of the inflammatory process. The ATP molecule has been considered a pro-inflammatory, while adenosine, which is the end product of ATP hydrolysis, appears to play protective action and anti-inflammatory. Acetylcholine (ACh), in turn, performs anti-inflammatory functions to inhibit secretion of cytokines by immune cells. In this context, the objective of this study was to investigate in serum and lymphocytes of 20 patients with MetS, the activity of the enzymes nucleoside triphosphate diphosphohydrolase (NTPDase), ectonucleotídeo pyrophosphatase / phosphodiesterases (E-NPP), adenosine deaminase (ADA), which control ATP and adenosine extracellular levels, and to analyze the activity of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) enzymes, which control the extracellular ACh level in order to effect the purinergic and cholinergic systems in patients with inflammatory action MetS. The results showed a decreased activity of the enzymes NTPDase and ADA in lymphocytes from patients with MetS. Moreover, we observed an increase in activity of the E-NPP and ADA in the serum of these patients. In addition, an increase in activity of both cholinesterase AChE and BuChE was observed in lymphocytes and serum, respectively. Finally, patients with MetS showed higher levels of CRP and uric acid as well as increased activity of MPO. Thus, the present results show the presence of an inflammatory state in patients with MetS by both the increase in inflammatory markers classics, and by immunomodulation triggered by purinergic and cholinergic systems. The lower activity of NTPDase in lymphocytes results in increased availability of extracellular ATP to stimulate inflammation and to influence the activity of other enzymes purinergic. Likewise, the high cholinesterase activities results in decreased availability of ACh extracellular, reducing the anti-inflammatory cholinergic effect. Thus, one may indicate that the purinergic and cholinergic systems have important effects in modulating the inflammatory process present in MetS, and the parameters mentioned in this research can useful in clinical medicine, to monitor the disease.